ANALISIS KINERJA KEUANGAN DENGAN METODE CASH VALUE ADDED (CVA) PADA PT BANK PERMATA TBK - Kaban, Dita Carolina Br; Nurlinda (Jurnal Budgeting, 2023)
This research is entitled "Financial Performance Analysis Using the Cash Value Added (CVA) Method at PT Bank Permata Tbk for the 2018-2022 Period". The aim of this research is to analyze the financial performance of PT Bank Permata Tbk by reviewing financial reports using the Cash Value Added (CVA) method. The data used in this research is secondary data obtained with technical documentation via the PT Bank Permata Tbk website. The population of this research is the financial statements of PT Bank Permata Tbk. The sample for this research is the financial position report, profit and loss report and cash flow report for the 2018-2022 period. The data analysis technique used is descriptive statistical analysis. Data processing technique using the Cash Value Added (CVA) method. The research results show positive numbers, which means the company is able to produce good financial performance for PT Bank Permata Tbk